2015
DOI: 10.1037/adb0000043
|View full text |Cite
|
Sign up to set email alerts
|

Childhood cognitive measures as predictors of alcohol use and problems by mid-adulthood in a non-Western cohort.

Abstract: This study examined the relationship between childhood cognitive functioning and academic achievement and subsequent alcohol use and problems in a non-Western setting. We examined longitudinal data from a birth cohort sample (n = 1,795) who were assessed at age 11 years on cognitive measures and then approximately 25 years later on lifetime alcohol use and alcohol use disorder symptom count. The sample is from Mauritius (eastern Africa), which allowed us to examine these relationships in a non-Western society … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…That we examined a low‐level drinking sample of adolescents presumably also accounts for the fact that we did not replicate that verbal comprehension predicted alcohol use problems at follow‐up (Luczak et al . ). There was a trend towards significance for family history of alcoholism that has been shown to be a reliable predictor for alcohol use problems in previous publications (Nurnberger et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That we examined a low‐level drinking sample of adolescents presumably also accounts for the fact that we did not replicate that verbal comprehension predicted alcohol use problems at follow‐up (Luczak et al . ). There was a trend towards significance for family history of alcoholism that has been shown to be a reliable predictor for alcohol use problems in previous publications (Nurnberger et al .…”
Section: Discussionmentioning
confidence: 99%
“…As a recent study found evidence that verbal IQ was predictive of later alcohol problems (Luczak et al . ), we also added the index score for verbal comprehension to our path model, which was derived from the subtests ‘vocabulary’ and ‘similarities’.…”
Section: Methodsmentioning
confidence: 97%
“…The latter includes genes and shared environment [25], socioeconomic status [26, 27] and childhood problems, including mental illness, cognitive difficulties and lower academic achievement preceding SUD [28-32]. Also, several of these environmental and constitutional factors have been associated with early school leaving [33, 34].…”
Section: Introductionmentioning
confidence: 99%
“…However, the proper way in which to interpret such findings is under discussion. Support has been found for both the long-and short-term effects of substance use, other scholars relate findings to factors preceding or co-occurring with substance use, such as childhood functioning, genes, socioeconomic status, environmental variations, and schooling (Battin-Pearson et al, 2000;De Witte, Cabus, Thyssen, Groot, & van den Brink, 2013;Fried et al, 2002;Jackson et al, 2016;Kubicka, Matejcek, Dytrych, & Roth, 2001;Latvala et al, 2009;Lin et al, 2010;Luczak et al, 2015;Meyer et al, 2012, Mokrysz et al, 2016Rogeberg, 2013;Tarter et al, 1995;Tarter et al, 2003).…”
Section: Intellectual Functioningmentioning
confidence: 99%